"You will eat shoe polish if you think it would help"—Familiar and lesser‐known themes identified from mixed‐methods analysis of a cluster headache survey. Issue 2 (27th January 2021) - Schindler, Emmanuelle A. D.; Cooper, Vanessa; Quine, Douglas B.; Fenton, Brenda T.; Wright, Douglas A.; Weil, Marsha J.; Sico, Jason J.
Abstract: Objective: To characterize patient‐reported ideas and concerns about cluster headache, treatment options, and management strategies. Background: Cluster headache patients experience severe pain and often suffer additional consequences from their disease. Patients have identified methods to cope with and combat cluster headache that are not widely known. Methods: Secondary analysis was performed using deidentified data from the online Clusterbusters Medication Use survey, wherein 10 questions allowed for freely written comments. Using mixed‐methods techniques, neurologists with expertise in headache medicine identified themes from these comments. Subgroup analysis sought to identify variables associated with specific themes. Results: Among 2274 free‐text responses from 493 adult participants, 23 themes were identified. Themes commonly discussed in the literature included such topics as "nothing worked" (24.7%, 122/493), "side effects" (12.8%, 63/493), and difficulties with "access/cost" (2.4%, 12/493). Less widely recognized themes included the use of "illicit substances" (35.5%, 175/493) and "vitamins/supplements" (12.2%, 60/493) in disease management. Lesser‐known themes included "coffee" (5.3%, 26/493) and "exercise/physical activity" (4.7%, 23/493). Using strict significance criteria, no subgroup was associated with any theme. Several poignant quotes highlighted patient thoughts and experiences. Conclusions: This mixed‐methods analysis identified challenges endured by cluster headache patients, as well as a variety of patient‐directed disease management approaches. The volunteered information spotlights pharmacological, physiological, and psychological aspects of cluster headache that warrant further exploratory and interventional investigation.